Teacher Exemplarity and Religious Habituation as Hidden Curriculum in Early Childhood Moral Education - Dwistia, Halen; Mutiara, Yolanda (Berkala Ilmiah Pendidikan, 2026)
This study aims to analyze the formation of moral character in early childhood through teacher exemplarity and religious habituation as dimensions of the hidden curriculum at Yustisia Kindergarten in Kotabumi, North Lampung. The study employed a qualitative approach with a case study design to obtain an in-depth understanding of the implicit mechanisms of value internalization occurring in the school’s daily practices. The research subjects consisted of three teachers, one principal as the key informant, and twenty students who served as indirect observation subjects. Data were collected through eight weeks of participatory observation, in-depth interviews, and document analysis. The data were then analyzed interactively through the processes of data reduction, data display, and conclusion drawing. The findings indicate that teacher exemplarity represents the most dominant dimension in the formation of moral character (87.5%), followed by religious habituation (83.3%), the internalization process (78.3%), and the hidden curriculum (67.5%). These findings suggest that explicit and structured practices tend to produce more rapidly observable behavioral consistency, whereas implicit value formation requires longer time and continuous reinforcement. The process of moral character formation occurs gradually, beginning with imitation of the teacher as a role model, continuing through habituation via religious routines, and eventually developing into the internalization of values as a more stable moral disposition. This study emphasizes that moral education in early childhood is not solely determined by the formal curriculum but is also shaped by the quality of daily interactions and institutional culture as a medium of the hidden curriculum that reinforces values in a latent and contextual manner.